О задаче синтеза системы управления квадрокоптером - Ларин, В.Б; Туник, А.А. (Прикладная механика, 2017)
Наведено алгоритм синтезу управління квадрокоптером. Розглянуто 2 варіанта управління горизонтальним рухом апарату. У першому випадку задається кінцеве положення, а в другому - крейсерська швидкість. На прикладах проведено порівняння з результатами інших авторів. An algorithm of synthesis of quadrocopter control is given. Two variants of control of the apparatus horizontal motion are considered. In the first case, the final location is given and in the second case the cruise speed is given. On examples, a comparison with results of other authors is carried out.